A carbon dot-based fluorescence turn-on sensor for hydrogen peroxide with a photo-induced electron transfer mechanism. Issue 85 (10th September 2015) - Lan, Minhuan; Di, Yanfei; Zhu, Xiaoyue; Ng, Tsz-Wai; Xia, Jing; Liu, Weimin; Meng, Xiangmin; Wang, Pengfei; Lee, Chun-Sing; Zhang, Wenjun
Abstract : A carbon dot-based fluorescence turn-on sensor for hydrogen peroxide with a photo-induced electron transfer mechanism was developed. Abstract : A carbon dot-based fluorescence turn-on sensor for hydrogen peroxide (H2 O2 ) with a photo-induced electron transfer mechanism was developed. The sensor exhibits good selectivity, sensitivity, and rapid response to H2 O2 with a detection limit of 84 nM. The sensor maintains excellent sensing performance over a wide pH range.